Neutralizing antibody responses against SarS-CoV-2 spike receptor-binding domain 13 months after the recovery from the disease - Dehgani-Mobaraki, P.; Kamber Zaidi, A.; Porreca, A.; Monti, M.; Floridi, E.; Floridi, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Information regarding the kinetics and longevity of acquired immunity in recovered COVID-19 patients requires thorough analysis and documentation. This is an update to an ongoing monocentric pilot observational study, that longitudinally analyzed the presence of antibodies after SARS-CoV-2 infection. Study design. Antibody titers against nucleocapsid protein (NCP) of SARS-CoV-2 analyzed at 8 months was followed by adoption of a more specific immunoassay, anti-Spike-Receptor binding domain IgG CLIA for analysis at 12 and 13 months post infection. Methods. MAGLUMI® SARS-CoV-2 S-RBD IgG Chemiluminescence immunoassay (CLIA) was adopted for measurement of antibody titres at 12 and 13 months after SARS-CoV-2 infection. Results. 97% (34 out of 35) patients resulted positive for anti-SARS-CoV-2 RBD IgG at 12 and 13 months. Discussion and Conclusions. In areas with vaccine and resource scarcity, vaccination could be prioritized for those individuals who have never been infected or for the ones who have recovered but show the absence of protective antibodies.